Garça-vaqueira (Bulbucus ibis): a diversidade genética no estudo do comportamento reprodutivo e na caracterização da população invasora brasileira - Silva, Emmanuel Moralez da (2013)
The genetic diversity of the cattle egret (Bubulcus ibis) was analyzed to investigate reproductive behavior and characterize Brazilian populations of the species. Genotypes at seven microsatellite loci were used to investigate the occurrence of more than one female laying eggs in the same nest, characterizing the occurrence of multiple maternity. DNA was extracted from swabs collected from the outer surface of eggs and sexed; males were excluded. Forty-eight clutches from two breeding seasons (2010 and 2011) were genetically analyzed. Thirty-nine eggs laid by a second or third female were recorded. In five nests, the first egg of the clutch was from a different female, the laying happening prior to that of the incubating female. Suggesting nest takeover by another pair of egrets that kept the pre-existing eggs together with its own clutch. In the other 43 nests, the hypothesis of brood parasitism was posed to explain why one or two additional females were found laying eggs in a nest. A 463-bp fragment of the mitochondrial DNA control region Domain I was amplified for 148 individuals from seven Brazilian populations to investigate genetic-population and demographic parameters. Genetic diversity indices, the population structure tests Fst and AMOVA, a haplotype network, mismatch distribution and neutrality tests (Tajima s D, Fu s Fs, Fu and Li s D* and F*, Ramos-Onsins and Rozas R2) revealed the following: i) a high level of diversity was recorded for the cattle egret in Brazil in comparison to other closely related species studied in the country; ii) genetic diversity levels determined for the Brazilian regions are similar; iii) genetic structuring was not observed between the seven studied populations; and iv) the different tests performed to determine demographic expansion revealed no significant results. This is the first genetic characterization study for Bubulcus ibis to date and the findings indicate a high degree of plasticity in reproductive behavior and confirm a marked dispersion behavior of the species, leading to the homogenization of Brazilian populations.